PROGRAM PELAYANAN KESEHATAN IBU DAN ANAK DI MASYARAKAT PESISIR - Nurmiah Dongoran; Putra Apriadi Siregar (Jurnal Kesehatan, 2023)
Health development is an effort to increase awareness, willingness and ability to live healthily so as to achieve optimal health status. In creating a healthy life for the community, many things need to be done, including health services. Minimum Service Standards are quality service provisions that are minimally implemented by local governments with a target of achieving 100% SPM annually. This study used a qualitative research method using a case study design (Case Study). This study aims to explore in depth matters related to the currently unachieved indicators of maternal and child health programs in coastal areas. Maternal and child health service programs in coastal communities are very important to improve maternal and child health in the area. Coastal communities often face unique health challenges, such as limited access to health services, poor sanitation, and a high prevalence of communicable diseases. Maternal and child health service programs can help address this challenge by providing access to essential health services, such as prenatal care, delivery services, and postnatal care. These programs can also provide education and support to mothers and families on topics such as nutrition, breastfeeding, and child development.